PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BERSERTIFIKAT PENDIDIK - Midi Hantono Midi Hantono (Manajer Pendididikan, 2015)
The general objective of this research is to analyze the relationship between headmasterleadership style and organization climate to the teacher of elementary school. The method of thisresearchuses descriptive quantitative study, data analysis techniques used SPSS 16.0 version byusing quality test and classic assumtion test. After doing research and done t test obtainedconclusion that there is significant and positive relationship between headmaster’s leadership styleith the teachers performance, while there is no significant relationship between organizationclimate and teachers performance. It means that the better the organization climate doesn’t maketeachers performance increase, the in F test, headmaster leadership style and organization climatesimultanous influence teacher’s performance significantly and positively.